Educational innovations for an inclusive learning environment: insights from the teachers' collaboration through lesson study - Basister, Michel P.; Petersson, Jöran; Baconguis, Rowena D. T. (Frontiers in Education, 2025)
Lesson Study (LS) is one of the collaborative practices that fosters deep interdependence among teachers. This deeper level of collaboration is vital in producing educational innovations that can lead to a more inclusive learning environment. Thus, this paper describes specific educational innovations that could promote inclusive learning environments developed and implemented by teachers during LS implementations. Using phenomenography, this study found various educational innovations emphasizing student-centered pedagogies, technology integration, and learning space modifications designed to address students' diverse needs during the teaching and learning process. Further data analyses also showed that the collaborations through LS fostered teachers' awareness of diverse learner needs, promoted student-centered planning, and encouraged input from veteran, novice, and special education teachers. These features of LS collaborations are crucial in developing inclusive and innovative practices. The findings from this study can help decision-makers optimize interventions, allocate resources strategically, and gain timely feedback on the impact of educational initiatives, such as LS, on the teaching and learning processes.